Phase formation and dielectric properties of Ba0.5Sr0.5TiO3 by slow injection sol-gel technique. - Balachandran, R.; Yow, H. K.; Ong , B. H.; Tan, Kar Ban; Anuar, K.; Teoh , W. T.; Ahmad Fauzi, M. N.; Sreekantan, S.; Swaminathan, V. (Springer Link, 2011)
A simple sol–gel process incorporating slow precursor injection technique was employed to synthesize homogeneous Ba0.5Sr0.5TiO3 nano powders. The Ba0.5Sr0.5TiO3 samples were subjected to calcination temperatures from 600 to 1,100 °C and sintering temperatures from 1,250 to 1,350 °C for the study of phase formation, crystallite size, particle distribution, and dielectric properties. Single phase Ba0.5Sr0.5TiO3 with a cubic perovskite structure was successfully synthesized after calcination at 800 °C. The average size of the nano particles is 42 nm with a narrow size distribution, and a standard deviation of 10%. The highest values recorded within the investigated range for dielectric constant, and dielectric loss measured at 1 kHz are 1,164 and 0.063, respectively, for Ba0.5Sr0.5TiO3 pellets calcined at 800 °C and sintered at 1,350 °C. Leakage current density measured at 5 V for the Ba0.5Sr0.5TiO3 pellet was found to be 49.4 pA/cm2.